Soy-Based Infant Formula: Are Phyto-Oestrogens Still in Doubt? - Testa, Ilaria; Salvatori, Cristina; Di Cara, Giuseppe; Latini, Arianna; Frati, Franco; Troiani, Stefania; Principi, Nicola; Esposito, Susanna (Frontiers in Nutrition, 2018)
Although Scientific Societies have stated that there are very few indications for the use of soy-based formula (SF) in infant nutrition, their utilization rates have been repeatedly found to be higher than expected. It is likely that a significant role in this regard is played by the belief that the use of SF during infancy can reduce the risk of the development of several diseases later in life. Although no definitive data that can substantiate these claims have been collected, many people perceive soy consumption to confer significant health benefits and might also use soy for infant nutrition. However, not all the problems regarding safety of SF in infants have been definitively solved. Among risks, the potentially toxic role of the phyto-oestrogens contained in SF is not definitively established. In vitro and animal studies have raised suspicions that SF could have potentially negative effects on sexual development and reproductive function, neurobehavioural development, immune function, and thyroid function. Several studies in humans have aimed to assess whether the results of animal studies can be applied to humans and whether SF can be used in infants following the official recommendations. The results are somewhat conflicting. The aim of this narrative review is to discuss what is presently known regarding the impact of phyto-oestrogens in SF on early and late child development. PubMed was used to search for the studies published from January 1980 to June 2017 using the key words: “ soy”, “soy formula”, “child”, “phytoestrogens”. Analysis of the literature showed that a global evaluation of the impact of modern SFs on human development seems to suggest that their use is not associated with relevant abnormalities. Only children with congenital hypothyroidism need adequate monitoring of thyroid function.